2020
DOI: 10.1177/0961203320928423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of web-based education and counselling for patients with systemic lupus erythematosus: self-efficacy, fatigue and assessment of care

Abstract: Objective The aim of this study was to determine the effect of web-based education and counselling for patients with systemic lupus erythematosus on self-efficacy, fatigue and assessment of care. Methods The study was conducted as a randomized controlled trial. The study sample consisted of 80 patients divided into two groups: the experimental group ( n = 40) and a control group ( n = 40). Randomization was performed by simple random sampling. At the beginning of the study (month 0), data-collection forms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Concerning studied females fatigue the current study showed that, there were statistically significant differences in fatigue between pre and one month after self-care management with significant reduction in the level of fatigue in the studied females was observed post self-care management which supported hypothesis two which stated that studied females will exhibit improvement in fatigue and pain post implementation of self-care management. This result is in accordance with Kankaya and Karadakovan (2020) (7) , who studied "effects of web-based education and counseling for patients with systemic lupus erythematosus: self-efficacy, fatigue and assessment of care" and reported a significant reduction in the level of fatigue in the experimental group that had been observed in measurements after the intervention. Vol.…”
Section: Table (7)supporting
confidence: 89%
See 2 more Smart Citations
“…Concerning studied females fatigue the current study showed that, there were statistically significant differences in fatigue between pre and one month after self-care management with significant reduction in the level of fatigue in the studied females was observed post self-care management which supported hypothesis two which stated that studied females will exhibit improvement in fatigue and pain post implementation of self-care management. This result is in accordance with Kankaya and Karadakovan (2020) (7) , who studied "effects of web-based education and counseling for patients with systemic lupus erythematosus: self-efficacy, fatigue and assessment of care" and reported a significant reduction in the level of fatigue in the experimental group that had been observed in measurements after the intervention. Vol.…”
Section: Table (7)supporting
confidence: 89%
“…2 (Suppl) , May 2022 supported by Elsayed and Mesbah (2018) (33) who studied "effect of health education based intervention on selfcare among systemic lupus erythematosus clients" and revealed that three quarters of patients didn't have other chronic diseases. On the contrary, Kankaya and Karadakovan (2020) (7) who studied "effects of webbased education and counseling for patients with systemic lupus erythematosus: self-efficacy, fatigue and assessment of care" found that more than half of study sample had other comorbidities. Regarding risk factors that increase symptoms, the present study results clarified that, three quarter, more than two thirds and more than half of studied females had physical, emotional and hormonal risk factors for SLE respectively.…”
Section: Table (7)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the COVID-19 pandemic, all counseling sessions except the first session were held via Skype and WhatsApp. A previous study has shown that virtual education and counseling have a positive effect on self-efficacy and other variables in SLE patients [ 26 ]. Sessions were held on a weekly basis.…”
Section: Methodsmentioning
confidence: 99%
“…It is essential to recognize how significant counseling and education are for people diagnosed with Lupus. In a randomized controlled trial conducted by Kankaya et al (2020), the researchers wanted to determine the effectiveness of web-based counseling and education for patients with Lupus on self-efficacy, fatigue, and assessment of care. Participants were put into an educational intervention program where they were taught about everything Lupus-related.…”
Section: Self-efficacy and Lupusmentioning
confidence: 99%